ANALISIS PERKEMBANGAN INDUSTRI KECIL DAN RUMAH TANGGA DENGAN PENDEKATAN DPSIR: STUDI KASUS DI KECAMATAN CIPARAY, KABUPATEN BANDUNG - Nurrohman Wijaya; Muhammad Aziz Ali Mutia (TATALOKA, 2016)
Micro, Small, and Medium-Sized Enteprises (UMKM) have a significant potential in contribution to local economic development in Indonesia. Within the development of economic sector and a dynamic population in Kecamatan Ciparay, UMKM of manufacturing industry is increasing as well, especially the small and home industries. Nevertheless, the industries still not put into practice optimally yet and give less contribution to the local economy. This article aims to analyze the development of the small and home industries in Kecamatan Ciparay with an analysis approach of DPSIR (Driver, Pressure, State, Impact and Response). The study applied descriptive research method. Questionnaire, interview and field observation were conducted in the study area. The results found that the development of the small and home industries is driven by some driver factors such as industrialization, socio-economic dynamic as well as local policy and strategy aspects. DPSIR model approach has identified some driver factors and the impacts of the small and home industries in a comprehensive system. A considerable attention of local government and decision makers becomes crutial focal point in order to support the UMKM in Kecamatan Ciparay.